Comparison of Irrigation Water Requirements: KP-01 and Cropwat 8.0 Methods Approach for Rentang Irrigation in Majalengka Regency - A, Patuh Rujhan; N, Andre Rangga; P, Agung Widi; Nurdiyanto, Nurdiyanto (Politeknik Siber Cerdika Internasional, 2025)
This study aims to compare the results of the calculation of irrigation water requirements between the KP-01 method and Cropwat 8.0 software in the Range Irrigation Area, Majalengka Regency. The research method used is a quantitative approach with a comparative method. The data used includes climate and rainfall data for the last 10 years (2014 - 2023) from Kertajati Meteorological Station, Jatiwangi Meteorological Station, and Ciwaringin Rain Station. The results showed that the irrigation water requirement calculated by the KP-01 method was higher than Cropwat 8.0. In the KP-01 method, the average irrigation requirement reached 0.85 lt/second/ha, with the highest requirement of 2.01 lt/second/ha (November I) and the lowest of 0.00 lt/second/ha. Meanwhile, the Cropwat 8.0 method shows an average water requirement of 0.36 lt/sec/ha, with the highest requirement of 1.14 lt/sec/ha (November) and the lowest of 0.05 lt/sec/ha (July). This difference is due to variations in the calculation methods in both methods.